2007
DOI: 10.1016/j.pscychresns.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

CSF sub-compartments in relation to plasma osmolality in healthy controls and in patients with first episode schizophrenia

Abstract: Preliminary evidence suggests that plasma Na + level/osmolality may have effects on brain morphology; thus we investigated the link between plasma osmolality and ventricle size in healthy controls and patients with first episode schizophrenia. A total of 16 patients and 28 healthy controls were examined with magnetic resonance imaging (MRI) and gave blood samples. Highresolution 3D SPGR images were obtained on a 1.5 Tesla scanner. Scalp-edited MRI volumes were used for estimates of intracranial gray, white mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study by Grant et al [39] showed that CSF volume increased in women with a normal menstrual cycle and not taking oral contraceptives. Other factors such as plasma sodium concentration or osmolality that affect water retention in the brain may also regulate CSF volume [7]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Grant et al [39] showed that CSF volume increased in women with a normal menstrual cycle and not taking oral contraceptives. Other factors such as plasma sodium concentration or osmolality that affect water retention in the brain may also regulate CSF volume [7]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, the lateral ventricles (LV), owing to the relative ease of their identification and segmentation using manual and automatic methods utilizing magnetic resonance imaging (MRI) contrast, have been shown to increase in volume with age in healthy adults [3, 4, 5]. Ventricular volume enlargement has been used as a surrogate marker in a host of pathologies [6, 7, 8]. CSF chemical and metabolic contents serve as robust biomarkers of neural degeneration [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological measurement using relatively-simple metrics such as the VBR is likely to be considered outmoded given the emergence of 3D surface and shape modeling approaches (Narr, Thompson et al 2001; Narr, Thompson et al 2001; Narr, Sharma et al 2003; Anticevic, Dierker et al 2008). For instance, in a study of plasma Na(+) level/osmolality in first-episode schizophrenics, Gunduz-Bruce and colleagues (2007) fit 3D surface mesh models to the ventricular system and noted no general differences between the patient and healthy control groups in ventricular size. However, a mixed model procedure indicated a significant group effect and a significant osmolality-by-group interaction in measures made on the ventricular surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Higher functioning patients may be more social and more exposed to opportunities for substance abuse (Arndt, et al, 1992) or more active in trying to cope with some of their symptoms by using substances (Ritzler, et al, 1977). Regarding cognition, earlier age at onset of psychosis has been associated with worse IQ (Woodberry, et al, 2008), attention (Frangou, et al, 2008, Oie and Hugdahl, 2008, Thaden, et al, 2006), executive function (Gunduz-Bruce, et al, 2007, Jeste, et al, 1998, Tuulio-Henriksson, et al, 2004), psychomotor speed of processing (Hoff, et al, 1996, Tuulio-Henriksson, et al, 2004, White, et al, 2006) and verbal learning and memory (Basso, et al, 1997, Tuulio-Henriksson, et al, 2004). Finally, motor abnormalities have been reported in drug-free first-episode schizophrenia (Honer, et al, 2005, Pappa and Dazzan, 2009, Peralta, et al).…”
Section: Introductionmentioning
confidence: 99%